On-Line Trajectory Generation in Robotic Systems : Basic Concepts for Instantaneous Reactions to Unforeseen (Sensor) Events - Kroger, Torsten (New York : Springer, 2010)
This monograph focuses on sensor integration in robotics, in particular in robotic manipulation control systems. We consider a mechanical system with multiple degrees of freedom equipped with one or more sensors delivering digital and/or analog sensor signals. There is no question that sensor integration and sensor-based control belong to the dominating domains for the future advancement of robotic systems. Although there has been much research on this objective, there is still one important question that has not been answered yet: If we consider a robot in an arbitrary state of motion, how can we calculate a trajectory, if we want the robot to react instantaneously to unforeseen sensor events
Includes Abbreviations and symbols 207-212p.; References 213-230p.
Keywords: Robotic systems; Trajectory generation; Computer Science